Market Concentration, Market Dynamism and Business Survival - Andrew Burke; Holger Görg; Aoife Hanley (Max Planck Institute of Economics, 2006)
The paper uses a unique dataset comprising the population of new ventures that enter the UK market in 1998. We argue that we would expect the effect of market concentration on firm survival to be different according to whether an industry is static (low entry and exit) or dynamic. In our empirical analysis we find support for this hypothesis. Industry concentration rates reduce the survival of new plants but only in markets marked by low entry and exit rates. Specifically, a 10 percent increase in the 5-firm concentration ratio or the Herfindahl index in a dynamic market, raises the survival rate of new ventures by approximately 2 percent. Our results suggest greater leniency towards more dominant firms in industries showing buoyant entry and exit rates.
Older version: http://hdl.handle.net/10419/3658
Keywords: L11; L25; M13; M40; 330; new firms; start-ups; survival; dynamism; competition policy; industry concentration; Unternehmensgründung; Unternehmenserfolg; Industrieökonomik; Schätzung; Großbritannien